Empowerment of Women's Culinary Business in Persit Kartika Chandra Kirana organization, Yogyakarta - Garbo, Anom; Hadikusuma, Sofwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This community service aims to empower Persit member mothers in improving their economic welfare. Cooking training was chosen as the approach in this program because it has the potential to provide better cooking skills as well as the opportunity to generate additional income through selling food. In this program, Persit women are given cooking technique training which includes choosing the right food ingredients, good cooking techniques, and a variety of healthy menus. In addition, they are also given knowledge about business management, marketing, and financial management. Through intensive mentoring, Persit member mothers are given support and guidance in developing their culinary business. This mentoring program has significant benefits.